"Wondermooi voorjaarsweer in Holland. Dus: in khaki tussen de tulpen". Waarschijnlijk Wim Dussel zelf - Dussel, Wim,
"Wondermooi voorjaarsweer in Holland. Dus: in khaki tussen de tulpen". Waarschijnlijk Wim Dussel zelf.